PREDICTION OF OUTCOMES OF NEPHROTIC GLOMERULONEPHRITIS SYNDROME IN YOUNG CHILDREN - Sh.M. Ibatova; Mamatkulova D.Kh; Mamatkulova F.Kh. (Western European Studies, 2024)
Glomerulonephritis still plays a significant role in the development of chronic renal failure in children. Detection of chronic kidney pathology at the initial stage is important for increasing the effectiveness of preventive and therapeutic measures aimed at slowing down the progression of the disease. Patients with acute GN (74) with nephrotic syndrome aged from 2 to 5 years were examined, of which 30 were boys and 44 were girls. The patients were divided into 2 groups. The first group included 35 patients who had no relapses of the disease for two or more years, the second group of patients (39) in whom complete remission was not achieved and a chronic form of the disease (CGN) developed. The development of the forecast algorithm was carried out using the method of sequential Wald analysis. The share of glomerulonephritis (GN) remains significant in the development of chronic renal failure at all ages.
Keywords: Glomerulonephritis; nephrotic syndrome; patients